2013
DOI: 10.1007/s10803-013-1797-8
|View full text |Cite
|
Sign up to set email alerts
|

Intervention for Infants at Risk of Developing Autism: A Case Series

Abstract: Theory and evidence suggest the potential value of prodromal intervention for infants at risk of developing autism. We report an initial case series (n = 8) of a parent-mediated, video-aided and interaction-focused intervention with infant siblings of autistic probands, beginning at 8-10 months of age. We outline the theory and evidence base behind this model and present data on feasibility, acceptability and measures ranging from parent-infant social interaction, to infant atypical behaviors, attention and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
66
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 84 publications
(72 citation statements)
references
References 44 publications
4
66
0
2
Order By: Relevance
“…Those children were diagnosed with ASD ( n = 248; [34, 3640, 4245]) or identified as being at risk of ASD based on either the presence of early markers ( n = 156; [10, 41, 46]) or because they were infant siblings of probands with ASD ( n = 80; [47, 48]).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Those children were diagnosed with ASD ( n = 248; [34, 3640, 4245]) or identified as being at risk of ASD based on either the presence of early markers ( n = 156; [10, 41, 46]) or because they were infant siblings of probands with ASD ( n = 80; [47, 48]).…”
Section: Resultsmentioning
confidence: 99%
“…Gender was reported for 253 of the 277 toddlers involved [10, 36, 37, 3945, 47]; 192 children were male (76%) and 61 were female (24%).…”
Section: Resultsmentioning
confidence: 99%
“…Because few studies focused exclusively on this age group, studies in which participants included some children aged .3 years were assessed as long as there was sufficient information to draw inferences about younger children. The group reviewed additional reports, which have not been listed in Table 1, including single-subject studies, [39][40][41][42][43][44] other relevant studies, 16,[45][46][47][48][49][50] metaanalyses, 51,52 and reviews. [53][54][55][56] Compared with early intervention models evaluated for preschool-aged children (aged 3-5 years), programs for children aged ,3 years were more likely to use developmental approaches, more intensively involve parents, and target social communication.…”
Section: Methodsmentioning
confidence: 99%
“…Three studies, focused on short-term interventions (≤12 sessions) for high-risk infants and toddlers, failed to identify effects on parents’ implementation of child-responsive strategies to children aged 8–25 months when compared to business-as-usual, or no-treatment groups (Carter et al, 2011; Green et al, 2013; Rogers et al, 2012). The remaining studies, most of which also were short-term interventions, identified intervention effects on parent responsivity during interactions with their child and/or on child behaviour.…”
Section: Naturalistic Developmental Behavioural Intervention (Ndbi) Amentioning
confidence: 99%